1988
DOI: 10.1002/bit.260320807
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale production of monoclonal antibodies in suspension culture

Abstract: Monoclonal antibodies are being manufactured for clinical trials in suspension culture at the 1300-L scale. Suspension culture offers some advantages relative to high-density mammalian cell culture methods; in particular, the ability to closely monitor the behavior of cells in a homogeneous environment. Computer control and on-line mass spectrography of exit gases provide instantaneous information about the culture metabolic activity. Air sparging and agitation by marine impeller provide aeration sufficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…The slope of this plot provides the specific oxygen rate which was determined to be around 0.15 mM 02/109 cellsh. This number compares well with the reported values of 0.1-0.36 mM 0,/109 cellsh (Backer et al, 1988) and 0.06-0.3 mM 02/109 cellsh (Spier and Griffiths, 1982).…”
Section: Oxygen Uptake By Hybridoma Culturessupporting
confidence: 89%
“…The slope of this plot provides the specific oxygen rate which was determined to be around 0.15 mM 02/109 cellsh. This number compares well with the reported values of 0.1-0.36 mM 0,/109 cellsh (Backer et al, 1988) and 0.06-0.3 mM 02/109 cellsh (Spier and Griffiths, 1982).…”
Section: Oxygen Uptake By Hybridoma Culturessupporting
confidence: 89%
“…The liquid surface at the bottom of this vortex was rapidly fluctuating with bubbles detaching and entraining into the culture medium. From high speed photographs taken of the reactor containing 1.0 L culture medium at agitation rates up to 220 rpm, we observed that the bubbles had an average diameter of [1][2][3] mm. In addition, the vortex did not come into contact with the blades of the impeller, which means that bubbles detached from the vortex solely as a result of the instability of the gas-liquid interface.…”
Section: Cell Growth At Low Agitation Rates In the Presence Of A Vortmentioning
confidence: 99%
“…Such a methodology would lead to a real gain in universality for the compartment models, but also introduces some difficulties, which are discussed in the Section 3.3. Compartment models have been used to simulate the macromixing inside industrial reactors of various configurations: liquid volume from 3.2±90 m 3 and with 1±4 Rushton impellers [33,38,41,43]. Realistic results, i.e., in rather good agreement with experimental data, were reported in all these studies, with several different sensor positions in the reactor, mainly with tracer pulses injected at the top of the tank.…”
Section: Model Descriptionmentioning
confidence: 87%
“…The fed-batch technique dominates in industrial processes dealing with biological material, e.g., for the production of antibiotics [1], insulin [2] or monoclonal antibodies [3]. The technical and economic reasons for this are well explained by Winkler [4].…”
Section: Concentration Gradient Formation In Bioreactors and The Consmentioning
confidence: 99%